Farm economic evaluation of elderberry production - Apáti, F. (International Journal of Horticultural Science, 2014)
In this present study the efficiency as well as the farm economic advantages and disadvantages of elderberry production are examined. Our objective is to determine the fact that under what conditions the elderberry production may be profitable regarding the present economic and market situations. Our analysis was carried out by a simulation model based on a farm-level data gathering in production enterprises. The total investment cost of an up-to-date, elderberry orchard of traditionally cultivated without irrigation is between 1000 to 1700 thousand HUF per one hectare and turning to productivity is expected within 4-5th years. These orchards are able to produce yields of 8,0 to 9,0 tons per one hectare in the average of the productive years, which makes reaching a revenue of 800 to 1000 thousand HUF possible regarding a per kg average selling price of 80 to 110 HUF. By this a net profit of 200 to 400 thousand HUF may be realized in case of a per hectare production cost of 600 to 700 thousand HUF. At the end of the lifetime of the orchard (12-15th year) an internal rate of return of 10 to 4%, an NPV of 1500 to 2000 thousand HUF per one hectare are typical in an average case, and the payback may be expected in the 6th to 8th year. From the farm economic aspect the elderberry may be considered as an extensive sector, which advantages are low capital and labour need, early recovery, good-acceptable profit on capital and cost to profit ratios, but its disadvantage is low per hectare profit comparing to intensive fruit species and orchards. In this way in general farms of capital-extensive and avoiding risks choose elderberry production.